Surgical management of pancreatic neuroendocrine tumors: an introduction. Issue 12 (2nd December 2019) - Hain, Elisabeth; Sindayigaya, Rémy; Fawaz, Jade; Gharios, Joseph; Bouteloup, Gaspard; Soyer, Philippe; Bertherat, Jérôme; Prat, Frédéric; Terris, Benoit; Coriat, Romain; Gaujoux, Sébastien
ABSTRACT: Introduction : Neuroendocrine tumors of the pancreas (pNETs) represent only 1% to 2% of all pancreatic neoplasms. These tumors can be classified as functional or nonfunctional tumors; as sporadic or from a genetic origin; as neuroendocrine neoplasms or carcinoma. Over the last decade, diagnosis of pNETs has increased significantly mainly due to the widespread use of cross-sectional imaging. Those tumors are usually associated with a good prognosis. Surgery, the only curative option for those patients, should always be discussed, ideally in a multidisciplinary team setting. Areas covered : We discuss i ), the preoperative management of pNETs and the importance of accurate diagnosis, localization, grading and staging with computed tomography, magnetic resonance imaging, endoscopic ultrasound, and nuclear medicine imaging; ii ), surgical indications and iii ), the surgical approach (standard pancreatectomy vs pancreatic-sparing surgery). Expert opinion : The treatment option of all patients presenting with pNETs should be discussed in a multidisciplinary team setting with surgeon's experienced in both pancreatic surgery and neuroendocrine tumor management. A complete preoperative imaging assessment – morphological and functional – must be performed. Surgery is usually recommended for functional pNETs, nonfunctional pNETs >2 cm (nf-pNETs) or for symptomatic nf-pNETs.